Shear Strengthening of High-Strength Reinforced Concrete Deep Beams with Openings Using High-Performance Concrete Mortars - Ahmed Hamoda; Mohamed Emara; Mizan Ahmed; Aref A. Abadel (International Journal of Concrete Structures and Materials)
Abstract Reinforced concrete (RC) deep beams often necessitate openings in their web to facilitate building utilities. These openings compromise the shear resistance of the beams and, therefore, should be strengthened in their critical shear zone. This study proposes externally bonded high-performance concrete (HPC) mortars layers strengthened with steel wire mesh to strengthen the shear capacity of high-strength RC deep beams with openings within their shear span. To facilitate this, an experimental program consisting of testing ten high-strength RC deep beams was carried out. The test parameters include the effects of opening, types of HPC mortars, namely, engineered cementitious composites (ECC) and ultra-high-performance fiber-reinforced concrete (UHFRC) mortars, the configuration of the opening (circular, square), and the size of the openings. Two strengthened beams were fabricated without openings, while the remaining incorporated various opening configurations. The results demonstrated the shear performance of the beams increases using the proposed strengthening technique. The increases in ultimate load capacity ranged from 5 to 68%, elastic stiffness improved between 8 and 97%, and energy absorption capacity enhanced from 7 to 127%. Increasing the opening size reduces the strength, stiffness, and energy absorption capacity of the beam. Furthermore, beams with circular openings exhibited better performance than their square counterparts. The specific design and strengthening strategies employed effectively improve their load-bearing capacity concerning the opening size ratio. Application of the HPC mortars with higher compressive and tensile strength further results in the improvement of their shear performance. In addition, a finite element model (FEM) was developed to simulate the performance of tested beams and compare the accuracy of the FEM against the test results. It was found that the adaptation of the Concrete Damage Plasticity (CDP) model with the parameters adopted in this study can accurately predict the behavior of the tested beams. An average error of only 4% was obtained for the experiment-to-predicted load for cracking and ultimate load. Furthermore, based on the parametric study performed on beams with circular openings strengthened with ECC layers, it is proposed that for practical design purposes the thickness of the ECC layer to the thickness of the beam (t ECCC/t beam) ratio should not exceed 0.32.